SENSITIVE KINETIC SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF DIPHENHYDRAMINE IN REAL SAMPLES - César A. Soto; Renato A. Saavedra; Cristian A. Poza; David R. Contreras; Diego P. Oyarzún; María I. Toral (Journal of the Chilean Chemical Society, 2019)
Kinetic spectrophotometry methods have levels of accuracy and sensitivity which are comparable to those of other methods and have been used in the quantification of different pharmaceutical analytes in different matrices. This work describes an indirect kinetic spectrophotometric method for the determination of diphenhydramine by the alkaline oxidation with permanganate in pharmaceutical formulations (injection) and tap water spiked samples. Measurements of changes in absorbance at 610 nm were used as criterion of the reaction progress. The optimization of chemical variables of oxidation reaction was realized using experimental design by multivariate analysis. The optimized values were 20 min of reaction time, KMnO4 1.00x10−3 molL−1, Na2SO4 0.20 molL-1 and NaOH 0.20 molL-1. Under these conditions calibration curves were constructed. The detection limits obtained in pharmaceutical formulations (injection) and tap water spiked samples, were 9.65x10-7 mol L−1 and 1.23x10-6 mol L−1, respectively. The method is simple and does not require expensive instruments or complicated extraction steps of the reaction product.